NATO defence planning between Wales and Warsaw: Politico-military challenges of a credible assurance against Russia - Rainer Glatz; Martin Zapfe (Stiftung Wissenschaft und Politik (SWP), 2016)
The far-reaching measures agreed by NATO at the Alliance's 2014 Summit in Wales substantially increase operational readiness but fall short in guaranteeing the security of all member states against Russia. The Alliance therefore faces difficult discussions before the next Summit in Warsaw in July 2016. Member states will have to improve capabilities and the operational readiness of their armed forces, which will come at a cost. Indefinitely avoiding the question of the role of nuclear weapons in defensive planning will not be possible. And finally, a credible assurance for the exposed Baltic States may not be feasible in the framework of the NATO-Russia Founding Act. As a transitory step, compromises can be reached, perhaps in the form of establishing an extensive infrastructure for a substantial pre-positioning of materiel. In the absence of a fundamental improvement of NATO's relationship with Russia, however, further measures will likely become necessary. (SWP Comments)
Keywords: 320